Розробка інформаційної системи для формування графіку тренувань та розподілу занять між спортивними майданчиками - Макаренко, С. О.; Іванов, В. Г. (ХНУРЕ, 2025)
This online sports field booking system simplifies the rental process and allows users to rapidly and conveniently reserve an available field for a needed time. This approach optimizes the booking management process, reduces the administrative burden on field owners and provides transparency for users. The application implements the abilІТy to view all available sports fields, book by time and location, abilІТy to pay online, and view history of orders. Admins can manage reservations and update field availabilІТy in the system.
Keywords: тренування; спортивний майданчик; інформаційна система